Antibacterial Potential of Fermented and Non-Fermented Allium sativum var. Solo Against Staphylococcus epidermidis - I Gede Ngurah Putra Nata Sudana; Sabariah; Musyarrafah; Mulianingsih, Wiwin (Jurnal Kesehatan Prima, 2025)
Acne vulgaris is one of the most prevalent skin diseases worldwide, often treated with antibiotics to suppress the growth of Staphylococcus epidermidis. However, the irrational use of antibiotics has led to the alarming rise of antibiotic resistance, necessitating alternative solutions. Herbal plants, such as single bulb garlic (Allium sativum var. Solo garlic), offer promising antibacterial properties due to their allicin content. Fermentation of garlic has been shown to enhance its antibacterial activity. This study aimed to compare the antibacterial potential of non-fermented and fermented single bulb garlic extracts against Staphylococcus epidermidis using a True Experiment with a Posttest-Only Control Group Design. The well diffusion method was applied to 24 samples divided into six groups: non-fermented and fermented extracts at concentrations of 60%, 80%, and 100%, with clindamycin and sterile aquadest as controls. Results demonstrated that all garlic extract groups exhibited sensitivity (>21 mm). Inhibition zones for non-fermented extracts were 29 mm, 33 mm, and 33 mm, while fermented extracts showed significantly larger zones of 38 mm, 40 mm, and 40 mm, respectively. Statistical analysis confirmed a significant difference (p < 0.05) between non-fermented and fermented groups. The findings highlight the enhanced antibacterial efficacy of fermented garlic, making it a potent alternative to combat Staphylococcus epidermidis.